Taytacha Qoyllur Rit'i: Rocks and dancers, beliefs and continuity - Gow, David D. (1974)
Until recently, anthropological and historical research in Peru collected the point of view of the victor, the conquered Spanish or the mestizo of the republican era. In recent years the perspective changed radically and emphasis was given to the so-called vision of the vanquished, the point of view of the conquered or the peasantry.